Adolescent intermittent ethanol exposure induces sex-specific and time-dependent changes in affective behaviors and metabolomic profiles - Shobande, Mariah J.; Kumari, Anjali; Pearson, Michael; Baker, Janae A.; Hall, Nzia I.; Waters, Renee C.; Emehel, Chloe E.; Hill, Dashear; Fowlkes, Myla E.; Dean, Tiffany; Cannady, Reginald; Wang, Bo; et al. (Frontiers in Behavioral Neuroscience, 2026)
Adolescent binge drinking in humans is associated with adverse outcomes, here we examined sex- and withdrawal-dependent changes in affective behaviors and metabolomic profiles in male and female mice following AIE exposure. Male and female C57BL/6 J mice were exposed to intermittent ethanol vapor inhalation from postnatal (PND) 28–42, a model of intermittent binge-like ethanol exposure during adolescence. Affective behavior was assessed using the open field test (OFT), light/dark test (LDT), and tail suspension test (TST) during short-term withdrawal (PND 49–53) and again during long-term withdrawal (PND 91–95). Serum samples were collected 24 h after the final exposure cycle (PND 43), fecal samples were collected during each OFT, and liver samples were collected at euthanasia (PND 119; ~80 days after exposure) for metabolomic analysis. Ethanol sensitivity in adulthood was additionally assessed using loss of righting reflex (LORR) on PND 116. Overall, AIE produced modest, sex- and withdrawal-dependent behavioral effects, whereas metabolomic differences were most pronounced in males shortly after exposure and diminished with longer withdrawal. These findings support future work testing whether early metabolomic shifts track later behavioral vulnerability.